Download as pdf or txt
Download as pdf or txt
You are on page 1of 14

2.1.

INTRODUCTION

alehra is basically two values i.e., (0, 1) function.


Previously it had it's application to
nfs and sets which are either true or false. Now-a-days it has wide applications to switching
netvorks etc. Basically, there are three operations in the case
of Boolean algebra (1) AND
OR and (in) NOT, which are symbolically written as (), +),()respectively.
2.2. DEFINITION OF BOOLEAN ALGEBRA
Anv non-empty set Bwith two binary operations i.e., (+ and'. ')
is called Boolean algebra [B, +,*,']
with one unary operation**",
provided that operations, satisfy the following postulates.
1, Closure. A set B is closed with respect to a binary
the binary operator
operator if, for every pair of elements of B,
specifies rule for
obtaining a unique element of B.
a

2. Commutative Law.A binary operator+and o n a set B is


said to be commutative whenever.
a+b b +a
a.b =b-a for all a, b EB
3. Associative Law. A binary operator + and on a set B is said to be associative whenever
a+(b+c) =(a +b) +c
a-(b c) = (a b).c for all a, b,c eB
4.
Identity Elements. a+0 0+a =a
a 1 =
1 a=a for all a eB
1OT
addition'0' is identity element and for
multiplication 1 is identity element.
Complement. For each a E B there exists a or a' eB, such that
a+a' =1
a a ' = 0 for all a eB
6. Distributive Law.
a (b+c)= a-b+a:c
a+(b c)= (a + b)-(a + c)
it is
c a n algebra, addition is distributive over the multiplication whereas in general algebra
not so.
2-2 BOOLEAN ALGER
2.3. PRINCIPLE OF DUALITY
Boolean algebra remain true even if 4 d
result which is true for
It states that any of any theorem in
algebra is alsotogether
a theorem.
withThe interchange
theduality
of and I Le,
the dual Ifthe
principle 0has many applications. dual0'sofand0'alsBool
1's dual
by by e1-
interchanged of an alg
+ and .
operators and replace 1's by 0'3
ando
expression is desired,
we simply interchange
and a' eB
For example: for all a a+a'=l1

then
and replace
1 by 0,
Let us write".
'in place of*+'
a a'=0

remains unchanged
complement
Thus law of
2.4. BASIC THEOREMS

Theorem1.Idempotentlaw a a =a for all


aEB
(ii)
() a+a=a (1is identity w.r.t.(a+a)]
(a+a)-l a+a'=l
(a+a)=
Proof. (i) = (a +a) (a +a') (Distributive Law
= a+a.a
a-a'=0
Identity]
a+0 [0 is Additive

a-a
=a
by duality eB
(i)
Involution
law (a)=a forall a
Theorem
2.
('a+a'=1]

(a''
=
1 (a')y
Prool = (a +a')-(a')' Distributive Law]
= a-(a') +a' (a')' a-a'= 0
= a-(a')' +0
= a-(a')' +a-a' [Distributive Law]
= a -[(a') +a'] a+a'=

al ldentity
: lis Multiplicative

3. () a + 1
=1
Theorem

(i) a . 0=0 for all aEB ldentity


a+l = I ( a + 1) :T is Multiplicative
ata'-I}
Proof.)
(a + a')-(a + 1) Distributive Law)
=
a+ (a' 1) ldentity)
f1 is Multiplicative
=ata T'a ta'=1

(ii) a-0=0
by duality.
B O O L E A NA L G E B R A
2-3
Theorem4Absorption law

(i) a (a + b) =a for all a,be B


= a
b)
(a
1is Multiplicative Identity]
a+
)
b)=a 1+ab
() a +(a
Prool. = a(1 +b)
[Distributive Law]
=a 1 :1+b=1]
a.

+b) = a by duality
(i) a (a De-Morgan's law
Theorem5.
(i) (a b)' =a' +b for all a, be B.
(a+6) =a'b'
S t a t e s that (a' b') is the complement ofa +b. Therefore, we have to prove that

( a+b)+a'b'=1

0
(a +b)-(a' b')
=

Now, (a +b)+a'b'
=
[(a + b) + a'][(a +b) +b'] Distributive Law]
Ca +a') + b][a + (b + b)] [Associative Law]
[1+b][l+ a] ['a+a' 1]
= 1.1=1

Therefore, (a + b) + a'b' =
1 .)
Also, (a +b) (a'b') = a-(a'b') +b-(a'b) By Distribution Law]
(a-a')b' +(b:b')a' [Associative Law]
(0-b) +(0 a') Ca-a' 0
0+0 0.
Hence (a+ b) (a' b')= 0
By () and (ii) we conclude that (a'. 6) is the complement of (a + b) consequently

(a +b)'= a' b'


(i) (a -by= d'+b by duality.
Generalised De-Morgan's law
1.
(a+az +ag t. +an) af aj aj...d =

2. (a1 a2. . . . a ) =a + a2 + a3. ...+an

2.5. BOOLEAN FUNCTIONS


variable, Boolean function and its torms.
the words constant,
T Section we shall come across preliminaries preparatory to
the topic concernea.
eOre, it will be better to define some
of
algebra, is called a constant
Co element of Boolean
Any symbol to denote some definite
Bool
blean Boolean algebra.
0 and 1 are two constants in
algebra, Boolean algebra
are called ofthe
variable
Variable. ymbols
Syn used to denote any arbitrary element
variables ofBoolean algebra.
a,bb, c.* , } 2 . . A , B, C,..etc. are used for
binary operations(+and
finite applicationofthe
Com
ombinations of constants and variables with
2-6 BOOLEAN
Canonicalform.A Boolean function (1, 2 . . In) of n variables
5.
in the form of sum of products or product of sum in such
when ere
polynomial a

involved all he n-variables, either complemented or uncomplemented then


en itit isis
form or expanded form of the given Boolcan function, for example knowna
S(,y) = ay+x'y + xy'

S a , ) = (x+ y).(r'+ y).(+ y')

S(x, y, 2) xyz + x'yz


S(x, y, 2) = (x+ y+z)(r'+ y'+ z) (r+y'+z)

are canonical forms in two and three variables.


The canonical forms of Boolean function are basic form that one obtains from
readinga
from the truth table.
6. Standard form. In standard form number of variables (literals) in each terms maybe on
or any number of variables.
F(%,y,2) Xty+)yz +xyz
F(, y, 2) = x(r+y) (x+y'+z)

etc., are the examples of standard form.

2.9. MINTERMS AND MAXTERMSs


Minterms is the product of all the variables in primed or unprimed form. Each variable ba
orimed if the corresponding bit of the binary numberis a 0 and unprimed
ifa1.A symbolfor
mismj wherejdenotesthedecimalequivalentofthebinarymaumberofthe mintermdesigne
or example
ma = 100 =xy'z'

Table 2.3 show all possible combinations of minterms for three variables. Minterm also cals
standard product.
Table 2.3.Minterms and Maxterms for 3 variables.

Minterms Marterm
Term Designation Term Designatio
xy'z' mo x+ytz Mo
0 0
xy' +y+? M
x'yz' m2 x+y'+z M
x'yz m3 + y'+ M
0 0 xy'z' 4 x+y+z M4
0
ay' Ms
0
m x+y+z
xyz' m6 r+y'+z M6
Xyz m x'+y'+z M
Maxterms is the summation of all the
variables
normal) form. Maxterms also called standardpresented
in
primed (complement) or
primed

h
sums. Each
variable being unprimed
2-8
Comparing () and (i), we have, B0OLEA
Co+C. C=2
Since, x=2".

Therefore, 'Co+C C,=2


Hence the number of possible functions that can be formed with n-variables
iables totohebe .
the 2 functions of n-variables can be also expressed as a product of maxterms, Fo.
of exar
two variables, themumberofpossible Boolean functions is16(2).
All the 16 functions formed with two binary variables x
and y are listed in Table 25
Table 2.S. Boolean
expressions for the 16functions of two binary variables
Boolean functions Operator symbol Name
Fo0 Null
Comments
Binary constant 0
Fy X.y AND x andy
F =" x/y Inhibition x but not y
Fx Transfer
F r'y
Inhibition y but notx
Fs y Transfer
Fs =y'+x'y
y Exclusive-OR
F x+y x+y
X or
y but not b
OR
F (x+ y)
=
rory
xy NOR
F =y+xy' x Oy
Not-OR
Fo=y' Equivalence x equals y
Complement Not y
XCy
x'
Implication Ify thenx
Fis =x'+y Complement Notx
Fis x'+ Implication Ifx theny
NAND
Fis1 Not-AND
ldentity Binary constant 1-
SOLVED EXAMPLEES
Example 2.1. Simplify the following
( (a +b+(a +b)
(i) (ab'e')
(ii) ab + ab' + a'b +(ab'c)+
(iv) a b + a -b'+a' (abe)
Solution. () By De-Morgan's law. b+a'b.
(a+b' +(a +b')' =
(a' b') +[a' (b')]
(a' b')+ (a' b)
From invohutionlaw
a'[b' +b]=a'-l =a'
2-9
ROOLEANALGEBAA

+ (ab)
(ab'c)
From Idempotent Law]
)
(ad'e')+
-(ab'e')+ (ab'c) +(ab'c)+ (abe)
[From Distributive Law]
-ab'le'+c)+ac [b' b]
+

(a +a' =1]
ab' + ac
- a (b'+ c).
(From Distributive Law]
a'b
+ a'b
=
a (b +6') +
) ab+ab' a.l+a'b
b+b'=1]
= a+a'b
From Distributive Law]
-(a+a') (a +b)
= 1(a + b) = a +b

8'+a'.b + a'b'
a-b+a
(a)
= a (b+b') +a' (b+ 6) [From Distributive Law]
= a.1+a'.1
b+b'= 1]
a+a=l

Erample 2.2. Provethat (a+b)


+c=a
+(b+c)for all a,b,c, eB
Solution. Let (a +b) +c=x
and a+(b+c) =y.
a'x = a[(a +b) + c]
Now
From Distributive Law]
a-(a+b) +a c
=a+aC
FromAbsorption Law]
= a

and ay =
a.[a + (b +c)]=a a + a (b+c)=a+a.(b+c)
FromAbsonption Law) )
a

Comparing () and (i), we get,


a X = a y

Also a' x = a' [(a +b) +c]


From Distributive Law]
a ' (a + b) + a' .c
From Distributive Law]
a' a+a' b+a'.c

= 0 + a ' .b + a ' c

= a' b + a ' c

and a'y = a' la + (b+ ¢))


[From Distributive Law]
a'.a+a' (b+c)
= 0+a'.b+a':c

= a'b + a'c

Comparing (it) and (iv), we have


2-10
BOOLEAN Au
a'r a'y
+a'y
Now ar+ a'r ay
=

(a +a') y
From Distributive
(a +a') x
1x = 1:y

(a + b)+c =a+(b+c).
=b.
Example 2.3. 1f ar br
= and ar' =bx', then prove that a

bx and ar' = bx'


Solution. We have given
=
ar

Therefore, (axr) + (a x) = (bx) + (bx')

a (x+r) = b(x+x') From Distributivej,


a.l = b .1 ; a=b.

Example2.4. Prove that a =0;b=0 ifa +b=0


Solution. Ifa+b=0 then
a a+0
= a+b.b'

(a+b)-(a +b')=0-(a +b) =0 From Distributive la


b b+0 =b+a.a' =(b +a) (b +a')
(a +b)-(b+ a') = 0-(a' + b) = 0.

Ezample 25. Express (r+ y) (x +


z) in
canonical form in three variables.
Solution. The first factor is
missing z and second factor is missingy. Adding 0 in each
putting 2 in place of 0 of first factor and yy' in factor
place of 0 of second factor, we get
F(a, 2)
y, =

(x+ y)(x+ z)
(x+y+0)(a+0+z)
=
(x + y+ zz') (x + yy' + z')
=

(x+y+ z) (x+ y+ z')(x+ y+


z') (x+ y'+ z')
[By DistributiveLav
=

(x+y+ z) {(x + y+ z') (x


+y+ z')} (x+y' +z')
(x+y+ 2)(x+ y+
Example 2.6. Obtain the z)(x+ y'+ z) [By Idempotent La
canonical form of the Boolean function
Sx, y, 2) =[(x
y')+( z)T +yz
+ +
Solution. f (, y, 2) =
((x + y')+(y+ z')) + yz
=

x+ y'+ y' (EY +


yz [By De-Morgan' La-
=
[x y'+ +
y'zY + yz
BOOLEAN ALGEBRA

-
[x+ y' (1+z)} + yz
2-11
By Distributive Law)
-

[x+ y'-1}+ yz
-
[x +y'l+yz
x ( +yz By De-Morgan's Law]
r'y+yz
x'y1+1.yz
*'y (z + z') + (x+X") yz
*'yz + x'yz' + xyz +x'yz
=
x'yz + x'yz' + xyz
a+a =a)
Example. 2.7. Prove that the value of the complete canonical form in three
variable is l.
Solution. The complete canonical form of a Boolean function in n
variables contains 2" terms,
The complete cononical form in three variables x, z is
y, given by
yz +yz' + *y'z +xy'z' +x'yz +x'yz' +x'y'z +
x'y'z'
=

(z+z')+ y (z + z)+xy{z +z)+xy' (z+z') [By Distributive Law


=
yl+y' 1 +xy-1+x'y'.1=y + ay' +x'y + x'y'
= x y + y ' ) + x (y+y)

=
x-l+x' 1=x+x' =1
By Distributive Law]

Erample 2.8. Change the sum of products form ay'


+xy'+x'y into product
of sum fom.
Solution.ay' +xy' +xy =

(x+*') y'+x'y
=

1.y'+xy =y' +r'y =(y' +x) (y'+y)


= ( x ' + y ) . 1 = x ' + y'

Ezample 2.9. Write down the


functionf(x. y) given in POSform to its SOP form,
where
fx, y)={x+y)(*+ y)+y)
Solution.
Sx,y)=
Using Distributive Law (z+y) (*+ y)*+y)
S,y) =
(x+ y)(x'+ yy')
(x+y')r +0)
(x+ y)x'
Xx'+ y' x'
0+x'y'
which is SOP form
of the
given function.
l e 2.10. Express the Boolean function f (x, y, z) (x +
y).(x+7')+(y +3) in asum
of minterms. =
2-12
Salotion.
f( V, E) - (1+ r)(+:)+ (v+ 2')
BOOLEAN AL
(T)+y+:'
x+(1'+y)+z' By Distributive
1+{:' +
1) + z' =
x+ y +z' =*:1+ y.1+ z' 1
By Associative
(r+ ')+ y (r +x')+ z'(x +x')
+
+y +xy' +:'*+z'r'
nn+r'y +z'x + z'*' By Distributive
=

1+n' 1+ x'y 1+z'x.1+z'r'.1 :xy +xy


n+")+y' (:+z') +x'y (z +z')
n: nz' +xy'z +
+
+z'x (y+y') + z'x' (y+y')
n'z'+ x'yz +xyz' +
z'y+z'y'+z'x'y+ z'x'y
mz (nz'+ yz')
+
+xy'z +(xy'z' + y'') + x'yz + [By Distributive l=
(xyz' + x'yz") +r'y'
(By Commutative and
n + nz'+xy'z
+y'z'+x'yz + x'yz'+ Associative Las
m y mg +ms +
x'y'z' By Idempotent La
m4 m3+ m2 +m0 2 (0, 2, 4,
Ezample 2.11. Hhat is dual of
=

3, 7). 5, 6,
f (4, B, C, D, E) (4+
Solution. Using Duality Principle, the of B+C)(D' E).
=

dual f (4, B, C, D, E) A.B.C+ =

Example 2.12. Obtain the D'+E.


Solution. For getting the complement of (AB+CD) E
S(4, B, C, D, E) complement this expression, we make use of
of
(AB +CD) E
=

De-Morgan's theore=
f(4, B,C, D, E) (AB + =
CD) E
f(4, B, C, D, E) [(AB =

CD) E] +

(AB
=

Example 2.13. Demonstrate byCD) E' =(A' B'):(C'+ D') + E'


+ +
+

Boolean algebra. means of truth


table, the validity of
()a the Distributive law
(b+c) =a
Solution. Distributive-blaw+aof
c
(i)a +b c
=(a +b) (a +c)
Boolean algebra
()a (b+ c) =a -b +a c
Table 2.6.
Truth table for .(b+ c)
a =
ab
b+c
+
ac.
0 a.(b+c) a.b a.c a.bta.c
0
0
0
0
0 0
0 0
0
BOOLEAN ALGEBRA

almbination we find that a.(bc)and (a.b) +


(a.c)are equal over all 2-13
ofa. and e, the theorem is thus proved. possible values
()at. (a +
b). (a t c).

Thble 2.7.Truth table for


a +b.c-(a +b).(a+c)
b.c a+b.c
0 0 0
a+ba+c (a +b).(a +c))
0 0
1 0 0
0 0
1 0
(O 1
0
0 0 1
1
1
1
(a+b.c)and (a + b).(a+ c) are equal over all
proved. possible values of a, b and c the theorem is thus
Example 2.14. If A . B 0 and A C=0, =

then, evaluate the Boolean


S(4, B, C)= A' B.C+ A' B' + B'+C. expression for
Solution. Given AC 0o
or
A C 1
Therefore, A =
1
Now and C=1
A B =0

1.B 0
B 0 : A=1)
F (A.B.C) = (4' B.C+ B'+B' +C) A'
=
(1)' 0.1+(1)' (0)' + +1
=
(0)'
0-0.1+0.1+1+1=0+0+1+1=1.

Example 2.15. Given AB'+ A'B =C, show that AC'+ A'C
Solution. Given AB' + =
B,
A'B =
C
Substituting the value of C in AC' + A'C =
B we get,
LHS =
A [AB' +
A'[AB' A'B] A'BY + +

A[(ABY (A'BY] +A'AB'+ A'A'B


A[(A' +B)(A+ B')]+0.B'+ A'B
A[A'B'+ AB]+0+ A'B
AA'B' + AAB + A'B
0+ AB+ A'B

B(A+ A')
B.1
2-14 BOOLEAN A
- RHS

Hence. proved
alued variables A. B. C and D by s o
Find the vales of the two ing th
Eampe 2.16
rimersT ations
A+ AB =0
4BAC

AB AC-CD =
CD
olutsion FromEn (), 4' + AB =0

0
(4 4)(4 B)
=

1-(4 B)0
A'B 0

Thereiore A' = 0 or A =l and B=0

FromE( AB AC
1-0 1-C
C 0
Substinuting the value of A = 1,B =0

2nd C 0 in equation
() we get,
1-0-1-(0-0-D (0) D
0+1-1 0= 1-D
D 1
Erample 2.17. in Boolean algebra (B, +, .
)prove tha
(a) a-b=0a:0, b=0
(6) a'b=0 ea+b=1
(c)a+b =a+cand a-b =a-c eb=c.
Solution. (a) If a-b =0,then
a a-1

a-(b-6')
By Compem
(a-b)-b'
=
0-b'
[ByAssociative
= 0 [:abi
b =b 1
= b-(a a ' )

= (b-a) a'

= (a-b)-a'

0-a
= 0.

(b) a'b 0
(a' b) =0'
By De-Morgan
BOOLEAN ALGEBRA

(a')+b' = 1 2-15
a+b'
By Involution Law)
b - b+ba
(c)
b(b + a)
b-(a + b)
-
b-(a + c)
=
b-(a + c)
=
b-a + b.c ('a+b=a+c]
= a-b +b-c

a-c+b.c
=
(a + b).c [a-b =a-c]
(a +c)-c
=
ac + CC
a c +C
C+aC

c (1+ a)
= c.1 [ 1+a =1]
C.

Example 2.18. Prove the following


using the Boolean algebraic theorem:
(a) AB+ AC+ BC AB
= +AC (b) AB+{A+ B'). B} =1
() (4+BC) (B'+
A)(B' +C') A =
(B+C).
Solution. (a) LHS =
AB + AC + BC
=
AB+ AC + BC-1
AB +
AC +1.BC 1-a=a]
=
AB+ AC +(4 +
A) BC
=
AB + AC + (A (:l=a+a']
+ A) BC
AB AC
+ +
ABC + ABC
AB +
ABC + AC + ABC
[By Commutative Law]
=

AB(1+ C)+ AC(1+ B) (By Distributive Law]


AB-1+AC1
AB+ Aic
=RHS.
(6)
LHS =
AB+ {(A +
B'). B}
AB+14B+ B'B
AB +(AB +0)'
ra-a'=0]
2-16
- AB+ (AB)'
= 1
BOOLEAN
-RHS.

(c)
LHS = (4+ BC) (B' + A)- (B'+ Cc")
= (4 + B) (A+ C) (B'+ A) (B'+ C")
( 4 + B)(A + B') (A +C) (B'+ C") By Distribu
By Commtag
AA3+ABt - (4+ BB')(4+C)(B"+C')
By Distrib
(4 +0) (A+ C) (B'+ C:)
=

=4-(A+ C) (B'+C')
= (4:A+ A:-C)(B+C')
=
(4 + A.C) (B' + C")
By ldempole
A(1+C) (B' + C')
=A-(B'+ C')
=RHS.
Example 2.19. Simplify the following Boolean
(a) [CA' B')' +C(A+c)Y function.
(b) ABCD+ AB' CD+
A'BCD + ACE
(c)A' B'C'+A'BC' + A'BC+
AB'C'+ ABC"+ ABC.
Solution. (a) CA B') +
C(A+C)
=
[(A) (B)+ CA +
+
CC By De Morgan's law and Distributie
= [A +B AC + C
+

=[A+ AC+B+ C}
= [A (1 +C)+ B +CY
= [A +B + C]
=A'B' C.
(b) ABCD +
AB' CD+ A'BCD + A'CB'D
=
ACD
(B+B') + A'CD (B + B') [By Distributive
ACD 1+ A'CD 1 a+d
=
ACD+ A' CD
CD (A + A')
= CD 1

CD.
(c) A'B'C" + A'BC'
A'BC +AB'C'+ ABC+ dBC
+

=
A'B'C+ A'BC' + A'BC +
ABC+ AB'C'+ ABC [ B yC o m m u t a t i v e

=
A'C' (B'+ B) + BC (A'+ A) + ByDistributive-

=
A'C'-1+ BC-1 +AC'.1
AC (B'+ B)
=
A'C'+ BC +A-C'
ROOLEAN ALGEBARA

= A'C+ AC+ BC

= (A'+ A) C'+ BC
= 1C+ BC

= C"+ BCC

=
(C+ B)(C"+ C)
= (C"+ B)1

= C"+B
Example 2.20. Prove the following equations using truth tables:
(@)a + d'b =a +b
(b)xyz+xy+xy7 =y.
Solution. (a)
Table 2.7. Truth table for a tab=atb.
a'b +ab
0
0 0
0

0 0 1
Since the truth-v 0 0 1
and b. un-values of the Boolean
equations, (a + a'b) and (a+b) are Sa-

You might also like